Estudio de prefactibilidad para la instalación de una planta productora de papa amarilla (Solanum Phureja) prefrita congelada con cáscara - Egües Mejia, Francisco (2022)
At present, the country does not have a potato processing plant, due to the fact that it does not have adequate machinery to carry out the industrialization of this raw material. The project presented arises as an initiative for the implementation of a processing plant for this input in Metropolitan Lima seeking to offer a product that exploits the benefits and properties of the potato and in the same way generate a sense of quality and good taste in the target market, Population of Metropolitan Lima with socioeconomic level A, B and C in an age range of 20 to 49 years. Using the factor ranking methodology, determining factors for the correct location were evaluated, determining that the industrial plant will be located in the district of Santa Anita, in the province of Metropolitan Lima. The size of the plant will be defined based on the demand of the target market, being 137 930 bags of 2,5 kilograms for the year 2024. Based on this size, the design and distribution of the plant will proceed. The production of the final product will be carried out semi-automatically, with the frying operation being the key to the processing flow because it is the bottleneck. Using the Guerchet method, it was found that the ideal minimum area for the production area is 66,97 square meters. Finally, the economic and financial analysis shows that the project is viable because it shows acceptable results, being evaluated under an opportunity cost of the shareholders of 18,63 %. Finally, we will proceed to evaluate the profitability indexes of the project and the social indicators to achieve a greater analysis of the results. The pre-feasibility study in this project applies the concepts and tools of industrial engineering.